2022
DOI: 10.2174/1871527320666210928160159
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholinesterase Enzyme Inhibitor Molecules with Therapeutic Potential for Alzheimer's Disease

Abstract: : Acetylcholinesterase (AchE), hydrolase enzyme, regulates the hydrolysis of acetylcholine neurotransmitter in the neurons. AchE is found majorly in the central nervous system at the site of cholinergic neurotransmission. It is involved in the pathophysiology of Alzheimer’s disease-causing dementia, cognitive impairment, behavioral and psychological symptoms. Recent findings involved the inhibition of AchE that could aid in the treatment of Alzheimer's. Many drugs of different classes being analyzed in the cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…By re-testing these in control (slo loxP/+ , see Methods) and non-balanced BK GOF (slo E366G/+ ) male flies, we identified rivastigmine as a specific and dose-dependent suppressor of motor defects caused by BK GOF in Drosophila (Figure 1B-E). Rivastigmine is a reversible non-competitive inhibitor of AChE, elevating synaptic ACh by preventing its hydrolysis in synaptic clefts (Figure 1C) 18 .…”
Section: Pharmacological Suppression Of Motor Defects In Bk Gof Fliesmentioning
confidence: 99%
“…By re-testing these in control (slo loxP/+ , see Methods) and non-balanced BK GOF (slo E366G/+ ) male flies, we identified rivastigmine as a specific and dose-dependent suppressor of motor defects caused by BK GOF in Drosophila (Figure 1B-E). Rivastigmine is a reversible non-competitive inhibitor of AChE, elevating synaptic ACh by preventing its hydrolysis in synaptic clefts (Figure 1C) 18 .…”
Section: Pharmacological Suppression Of Motor Defects In Bk Gof Fliesmentioning
confidence: 99%
“…Studies have shown that marker genes of AD are generally APP gene on chromosome 21, the presenilin 1 (PS1) gene on chromosome 14 and presenilin 2 (PS2) gene on chromosome 1, and the susceptibility genes of sporadic AD are mainly apolipoprotein E (ApoE) gene on chromosome 19 (Prince et al, 2015; Qazi et al, 2018). Cholinergic theory believes that most of the cognitive impairments suffered by AD patients are caused by the increased activity of acetylcholinesterase (AChE) in the brain and the lack of acetylcholine (ACh), which leads to the lack of cholinergic neurotransmitters (Friedli & Inestrosa, 2021; Sivaraman et al, 2022). The oxidative stress theory is based on mitochondrial dysfunction.…”
Section: Etiological Mechanism Of Admentioning
confidence: 99%
“…Acetylcholinesterase (AChE) is a molecule that has important functions in AD. AchE promotes brain dysfunction by degrading acetylcholine (Sivaraman et al, 2022). Inhibition of AchE expression or activity is a potential strategy for the treatment of AD.…”
Section: Pharmacological Effects Of Sinomenine In Alzheimer's Diseasementioning
confidence: 99%